Estimating the long-term effects of a fruit fly eradication program using satellite imagery - Lina Salazar; Marcos Agurto Adrianzén; Luis Alvarez (Inter-American Development Bank (IDB), 2023)
This analysis applies a regression discontinuity approach combined with remote sensing data to measure the productivity impacts linked to a fruit-fly eradication program, implemented in Peru. For this purpose, satellite imagery was used to estimate a vegetation index over a 10-year span for a sample of 305 producers -155 treated and 150 controls-. The results confirmed that program participation increased agricultural productivity in the short and long terms, in a range from 12% to 49%. However, quantile regression methods suggest that most productive farmers were able to obtain greater impacts.
Keywords: Q12; Q16; O13; 330; Agricultural Productivity; Impact Evaluation; Remote Sensing; Satellite Images; Peru